Combining Pentoxifylline With Vedolizumab for Crohn's Disease: Results of a Randomised, Placebo-controlled Pilot Study. (1st June 2022) - Berera, Shivali; Ioannou, Stephanie C; Morillo, Diana; Mantero, Alejandro M A; Pignac-Kobinger, Judith; Colina, Niurka; Santander, Ana M; Fernandez, Irina; Quintero, Maria Alejandra; Rodriguez, Jennifer; Kerman, David H; Damas, Oriana M; et al.
Abstract: Background and Aims: The efficacy of current biologics may be limited by targeting only one pathway. Pentoxifylline [PTX] interferes with tumour necrosis factor [TNF] gene expression. We performed a randomised, placebo-controlled pilot study to determine if PTX plus vedolizumab [VDZ] in patients with Crohn's disease [CD] is safe and improves response compared with VDZ monotherapy. Methods: Thirty adult patients with active CD were randomised to VDZ/PTX or VDZ/placebo and followed for 24 weeks. Endoscopic activity and inflammatory cytokines were measured at baseline and Week 24. Descriptive statistics were used to determine estimates of effect. Results: Demographics were similar but baseline disease activity was higher in the VDZ/PTX group. There was no difference in clinical remission at Week 14 (60.0% vs 66.67%, odds ratio [OR] 0.76, 95% confidence interval [CI] 0.16, 3.51) or steroid-free clinical remission at Week 24 in patients receiving VDZ/PTX. Improved clinical response was noted in the VDZ/PTX group at Weeks 6, 14, and 24 [Week 6: 20% vs 6.67%, Week 14: 26.67% vs 6.67%, Week 24: 40% vs 20%]. The rate of endoscopic remission was similar between the groups [40% vs 33.33%], with a greater mean decrease in Simple Endoscopic Score-CD [SES-CD] and C-reactive protein [CRP] with VDZ/PTX [SES-CD -3.17 vs -0.15, CRP -5.56 vs 0.46]. An increase in serum TNF-α concentration was observed with VDZ/placebo group; PTX mitigated this effect. No serious adverse events occurred. Conclusions: VDZ/PTX did not provide benefit over VDZ monotherapy in clinical or endoscopic remission but appeared to improve clinical response and was safe. These data should inform a fully powered study.